PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI SWALAYAN BERKAT KASIH TELUK DALAM - ALWINDA MANAO (LPPM Universitas Nias Raya, 2022)
Based on the results of an initial study at Swalayan Berkat Kasih Teluk Dalam in 2020, it seems that the level of employee motivation is relatively low. Supposedly, motivation questions how to direct subordinates, so they want to work productively in order to realize the goals that have been determined. The purpose of this study was to determine the effect of work motivation on employee performance at Swalayan Berkat Kasih Teluk Dalam. The type of research used is associative quantitative, using a questionnaire research instrument. The data analysis technique used is simple regression analysis. The results showed that the calculation for the work motivation variable was 8.169 and the significant level was 0.000. While the table value is 1.697 because the value of the account (8, 169) > table (1.697) and a significant level of 0.000 <0.05, then the decision is H, accepted and Ho is rejected meaning that the work motivation variable has a positive and significant effect on the employee performance variable at Swalayan Berkat Kasih Teluk Dalam. The conclusion of this study is that work motivation affects employee performance at Swalayan Berkat Kasih Teluk Dalam. The researcher suggests (1) It is necessary to provide work motivation at all times to employees of Supermarket Berkat Kasih Teluk Dalam in improving employee performance, both now and in the future; and (2) Further research is needed, if you are interested in continuing this research, it is better to expand more on the factors that affect employee performance apart from work motivation with a larger sample.